Armazenagem de hidrogênio em nanocompósitos MgH2- aditivos à base de Fe e Nb, produzidos por moagem de alta energia e laminação a frio - Floriano, Ricardo (2012)
Mg-based nanocomposites are considered promising materials for hydrogen storage in the solid state. In this work, Mg-based nanocomposites containing iron-based (Fe, Fe2O3, FeF3) and niobium-based (Nb, Nb2O5, NbF5) additives were processed by different processing routes involving high energy ball milling and severe plastic deformation techniques. The high energy ball milling techniques are represented here by the reactive milling under hydrogen atmosphere and by the cryogenic milling while the severe plastic deformation technique is represented here by extensive cold rolling. An alternative processing route including a previous short ball milling step before the cold rolling processing was evaluated. The study of the effect of additives according to the chosen processing routes and an extensive characterization of the hydrogen storage properties allowed a better understanding on the mechanisms which are responsible by the kinetics improvements related to the microstructural particularities. The materials prepared by the different processing techniques were characterized by micro and nanostructural analysis techniques such as, among others, x-ray diffraction followed by the Rietveld method, scanning and transmission electron microscopy. The desorption behavior was studied by differential scanning calorimetry and the kinetic behavior was investigated by absorption and desorption cycles. The correlation of the results obtained with the different processing routes showed that the beneficial effect of the additives in promoting the H-sorption kinetics is positively extended independently of the processing route; however, the acting mechanisms depend on strictly on the preparation methods and the combination of one or more factor related to the microstructure. Furthermore, the severe plastic deformation techniques showed a very good potential in comparison with the high energy ball milling techniques in processing Mg-based nanocomposites, resulting in materials with good hydrogen storage properties.